An updated procedure for zeaxanthin and lutein quantification in corn grains based only in water and ethanol - Carneiro, Ariadne M. [UNESP]; Lima, Bruna R. [UNESP]; Chibli, Lucas A. [UNESP]; Carneiro, Renato L.; Funari, Cristiano S. [UNESP] (Elsevier, 2023)
Corn grains are a major source of both the bioactive carotenoids zeaxanthin and lutein. Current methods to quantify these substances have some disadvantages related to sustainability and sample throughput. This work aimed to develop a green, efficient, rapid, and reproducible analytical method to quantify these xanthophylls in corn grains. Solvents recommended by the CHEM21 solvent selection guide were screened. The extraction by dynamic maceration and separation by ultra-high-performance liquid chromatography were optimized by design of experiments. Then, the entire analytical procedure was validated and compared with procedures used for the same purpose, including an official one, and applied to different corn samples. The proposed method was demonstrated to be greener, equal to or more efficient, faster, and more reproducible than the comparative methods. The extraction step could be scaled up for industrial production of zeaxanthin- and lutein-enriched extracts, as it uses only compatible food grade ethanol and water.
Keywords: Design of experiments; Green analytical chemistry; Sample preparation; UHPLC; Zea mays L.